(untitled) (Raparin Journal of Humanities (RJH), 2025)
The present study examines the morpho-phonological adaptation of English loanwords into Central Kurdish within the context of political news articles. The study focuses on how English lexical items are integrated phonologically and morphologically into the Central Kurdish Dialect (or CK), demonstrating the constant language contact and influence. For this purpose, a total of 9 political news articles are analyzed, drawn from three major Kurdish news outlets, namely, Rudaw, Channel 8, and Kurdistan 24 (K24), that were published during the first quarter of 2025 (January, February, and March). The selection of articles was based on their titles and likelihood of containing loanwords from English. The articles covered news events of local, regional, and international political news, depending on the categorization as appears on the websites. The analysis focuses on segmental and supra-segmental phonological adaptation processes such as substitution, stress modification, syllable restructuring, as well as morphological integration through Kurdish inflectional and derivational patterns. The findings demonstrate and highlight systematic adaptation strategies of English loanwords into Central Kurdish, shaped by both linguistic structures and the sociopolitical role of media, particularly political news websites, as they get the most readers’ attention nowadays.